SCIENCE AND INNOVATION AS DRIVERS OF ECONOMIC DEVELOPMENT IN THE AGE OF GLOBAL TURBULENCE: EVALUATION OF SIGNIFICANCE AND PROSPECTS - V. Ustenko (Вестник университета, 2016)
The present paper analysis possible trajectories of evolution of science and technology as drivers of economic development in the world. It substantiates the need and objective premises for the development and diffusion of basic innovations of the new technological paradigm in the world. At the same time it suggests that the feasibility of this scenario hinges on the ability of major countries to overcome existing structural imbalances and implement a new form of science and innovation policy, which at present stage is intertwined with industrial policy.